2022
DOI: 10.1007/s00415-022-11223-7
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the use of plasma pTau181 in retired contact sports athletes

Abstract: Background: Considering the wide range of outcomes following sport-related concussions, biomarkers are needed to detect underlying pathological changes. The objective was to analyze the use of plasma phosphorylated tau 181 (pTau181) as a non-invasive measure of underlying brain changes in a cohort of retired contact sports athletes at risk of neurodegeneration.Methods: This study included 54 retired contact sport athletes and 27 healthy controls whose blood plasma was analyzed for pTau181. A portion (N=21) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 44 publications
(70 reference statements)
1
12
0
Order By: Relevance
“…Specifically, p-tau181 showed a modest (AUC = 0.72) ability to discriminate mTBI patients with subtle injuries detected on MRI only from UIC, suggesting its potential utility in detecting more subtle injuries not observed on CT. This finding is in agreement with a recent study showing elevated p-tau181 in retired athletes with a history of repetitive concussions compared to controls and that an elevation in plasma p-tau181 is associated with brain abnormalities detected with MRI ( 26 ). Acute axonal injury and microstructural alterations of white matter are hallmark features of mTBI, but their subtle nature can often be detected only in research settings.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Specifically, p-tau181 showed a modest (AUC = 0.72) ability to discriminate mTBI patients with subtle injuries detected on MRI only from UIC, suggesting its potential utility in detecting more subtle injuries not observed on CT. This finding is in agreement with a recent study showing elevated p-tau181 in retired athletes with a history of repetitive concussions compared to controls and that an elevation in plasma p-tau181 is associated with brain abnormalities detected with MRI ( 26 ). Acute axonal injury and microstructural alterations of white matter are hallmark features of mTBI, but their subtle nature can often be detected only in research settings.…”
Section: Discussionsupporting
confidence: 93%
“…P-tau181 in CSF-derived EVs has also recently been shown as a potential monitoring biomarker in former NFL players at risk for CTE ( 25 ). Plasma p-tau181 was also recently shown to be significantly higher in retired contact sport athletes compared to healthy controls and was significantly associated with MRI brain imaging abnormalities in the athlete group ( 26 ). In military-related TBI, elevations in serum p-tau181 levels were observed in the military personnel at 2 and 7 days following repetitive blast exposure ( 27 ).…”
Section: Introductionmentioning
confidence: 96%
“…Similarly, the average number of TBIs is variable, with some researchers looking at the long-term effects of up to 3 TBIs [92] and others having participants with a history of 10 TBIs, on average [56]. Also, some studies were based on self-reported accounts of TBI, or occupancies and sport positions with high susceptibility to TBI, which were not supported by medical documentation (e.g., [59,69,74,85]). However, in contrast to a recent statement by the Concussion in Sport Group [122], there is evidence to demonstrate the effect of head impacts on the biomarker levels described in this review, indicative of a causal link between TBI and CTE and longterm neurological effects [13,28,59,[69][70][71][72][73][74]123,124].…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…Also, some studies were based on self-reported accounts of TBI, or occupancies and sport positions with high susceptibility to TBI, which were not supported by medical documentation (e.g., [59,69,74,85]). However, in contrast to a recent statement by the Concussion in Sport Group [122], there is evidence to demonstrate the effect of head impacts on the biomarker levels described in this review, indicative of a causal link between TBI and CTE and longterm neurological effects [13,28,59,[69][70][71][72][73][74]123,124]. Specifically, Nowinski et al [124] used the Bradford Hill criteria to analyze the causality between RHI and CTE.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…Advancements in ultrasensitive analytical platforms have enabled the quantification of blood-based TBI biomarkers (eg, glial fibrillary acidic protein [GFAP], ubiquitin C-terminal hydrolase L1 [UCH-L1], neurofilament light [NFL], total tau [t-tau], phosphorylated tau-181 [p-tau-181]) for SRC research at concentrations in femtogram range. 7 , 8 , 9 , 10 Common standards of practice in fluid biomarker research studies using these immunoassays use multiple technical replicates (≥2 measurements from the same specimen), which are used to calculate the mean point estimate used in statistical analysis. 11 , 12 This practice helps mitigate potential sources of intraassay bias due to preanalytical procedures or any complex biological interactions in the specimen matrix.…”
Section: Introductionmentioning
confidence: 99%